Development of Oral Colon Specific PH Dependent Microcapsules of NSAID Drug Naproxen - J. K. Saboji, R. B. Gadve, S. M. Patil (Journal of Applied Pharmaceutical Science)
The objective of present study is to develop oral colon specific pH dependant microcapsule of NSAID Drug Naproxen, to release drug in the colon and minimize or avoid local side effect by avoiding drug release in the upper git. Naproxen is encapsulated with Eudragit S 100 using O/W emulsion-solvent evaporation technique. Compatibility study was performed by I.R., D.S.C., X.R.D study. Microcapsules were evaluated for angle of repose, bulk density, tapped density, Carr’s index, particle size, drug loading, in-vitro drug release. The prepared microcapsules were white, free-flowing, and spherical in shape and particle size was in the range of 240.40-560.81µm. The drug-loaded microcapsules showed 69.88% to 98.73%. drug entrapment, angle of repose in the range of 28º.07” to 35 º.53”, bulk and tapped densities in the range of 0.4000 gm/cm3 to 0.4347 gm/cm3 and 0.4347gm/cm3 to 0.4787gm/cm3 respectively, Carr’s index ranges from 5.20 and 14.98. In vitro drug release studies were carried out up to 9th hr. in three different pH media, i.e., 0.1 N HCl (pH 1.2), phosphate buffer (pH 6.8 and 7.4). The drug-polymer concentration influences the particle size and drug release properties. All the formulations were following the Higuchi model of kinetic drug release.
Keywords: Naproxen, Eudragit S 100, Microcapsules, O/W Emulsion Solvent Evaporation, Release Kinetics.